2000
DOI: 10.4049/jimmunol.165.7.3923
|View full text |Cite
|
Sign up to set email alerts
|

Group BStreptococcusInduces Apoptosis in Macrophages

Abstract: Group B Streptococcus (GBS) is a pathogen that has developed some strategies to resist host immune defenses. Because phagocytic killing is an important pathogenetic mechanism for bacteria, we investigated whether GBS induces apoptosis in murine macrophages. GBS type III strain COH31 r/s (GBS-III) first causes a defect in cell membrane permeability, then at 24 h, apoptosis. Apoptosis was confirmed by several techniques based on morphological changes and DNA fragmentation. Cytochalasin D does not affect apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 65 publications
5
122
1
Order By: Relevance
“…2A). Since GBS has been shown to induce apoptosis in macrophages, 14,15 we wanted to confirm that the difference in survival between the 2 strains was not due to increased induction of apoptosis by the ST-12 strain. Using trypan blue staining followed by viable cell counting, we found that GBS infection significantly decreases macrophage viability over time compared to the (Fig.…”
Section: Gbs Genotypes Differ In Level Of Phagocytosis By Macrophagesmentioning
confidence: 99%
“…2A). Since GBS has been shown to induce apoptosis in macrophages, 14,15 we wanted to confirm that the difference in survival between the 2 strains was not due to increased induction of apoptosis by the ST-12 strain. Using trypan blue staining followed by viable cell counting, we found that GBS infection significantly decreases macrophage viability over time compared to the (Fig.…”
Section: Gbs Genotypes Differ In Level Of Phagocytosis By Macrophagesmentioning
confidence: 99%
“…DPPC can also inhibit GBS mediated cytokine activation (25,29), macrophage apoptosis (27) and epithelial cell invasion (25). It is interesting to speculate that a lack of DPPC inhibition of beta-h/c toxicity may in part explain the increased incidence and severity of GBS pneumonia and sepsis in premature, surfactant-deficient neonates (4).…”
Section: Beta-hemolysin/cytolysinmentioning
confidence: 99%
“…In vitro studies confirm that the GBS beta-h/c upregulates macrophage expression of iNOS and nitric oxide (24), lung epithelial expression of IL-8 (25), and blood-brain barrier expression of a wide range of neutrophil signaling factors (e.g, IL-8, GRO-alpha, ICAM-1, GM-CSF) (26). GBS beta-h/c triggers apoptosis of macrophages in vitro, a process which is dependent on protein synthesis, but independent of caspase-1, caspase-3 or MyD88 signal tranduction pathways (27,28). Beta-h/c further promotes the ability of GBS to invade pulmonary epithelial cells, a proposed early step in the pathogenesis of systemic infection (25).…”
Section: Beta-hemolysin/cytolysinmentioning
confidence: 99%
“…In addition, we could demonstrate that cleavage of Caspase 3 and Caspase 8 was increased (Figure 2). Induction of apoptosis by GBS could be previously demonstrated for macrophages, monocytes and fibroblasts, but not for other cell lines, which in consequences implicates a cell specific phenomenon [17]. It is remarkable that the septic GBS strain showed a stronger activation of Caspase 3, compared to the colonizing strain.…”
Section: Discussionmentioning
confidence: 72%
“…We assume that this stronger Caspase 3 activation is, among other factors related to the presence of ß-hemolysin, as previously demonstrated for macrophage [18] and monocyte apoptosis [19]. GBS-induced apoptosis is inhibited by the Caspase-3 inhibitor DEVD-CHO [17]. In consequence, induction of Caspase-3 might be responsible for tissue damage, leading thereby to dysregulation of hemostasis.…”
Section: Discussionmentioning
confidence: 87%